A COMPARATIVE STUDY OF CHANGES IN SOIL FERTILITY UNDER TWO FARMING PRACTICES IN THE KANO CLOSE-SETTLED ZONE - G. K Adamu; Maharaz A. Yusuf (European Scientific Journal, ESJ, 2014)
The influence of two farming systems (sole and mixed cropping) on soil properties was investigated in the Wudil area of the Kano Close-Settled Zone. Soil samples collected from plots under the two practices were subjected to physico-chemical analyses. The results indicate that soil under mixed cropping have higher levels of organic carbon, total nitrogen, Cation Exchange Capacity (CEC), exchangeable bases and available phosphorus than sole cropped plots. Mixed cropping is beneficial in enhancing soil fertility through reduction in soil erosion and higher organic matter build-up.